2018
DOI: 10.3389/fnagi.2018.00273
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Hyperglycemia Is Associated With White Matter Hyperintensity and Brain Atrophy in Older Patients With Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus is associated with neurodegeneration and cerebrovascular disease. However, the precise mechanism underlying the effects of glucose management on brain abnormalities is not fully understood. The differential impacts of glucose alteration on brain changes in patients with and without cognitive impairment are also unclear. This cross-sectional study included 57 older type 2 diabetes patients with a diagnosis of Alzheimer’s disease (AD) or normal cognition (NC). We examined the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
0
23
2
Order By: Relevance
“…Because brain tissue of AD show increased oxidative stress during the course of the disease [39], AD patients are more likely to be susceptible to the influence of glucose fluctuations on the brain. In fact, our previous study showed that glucose fluctuations during postprandial periods were independently associated with frontal white matter hyperintensity (WMH) in diabetic patients with AD but not in patients with normal cognition [40]. Frontal WMH is known to play a predominant role in motor dysfunctions in AD/aMCI patients [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Because brain tissue of AD show increased oxidative stress during the course of the disease [39], AD patients are more likely to be susceptible to the influence of glucose fluctuations on the brain. In fact, our previous study showed that glucose fluctuations during postprandial periods were independently associated with frontal white matter hyperintensity (WMH) in diabetic patients with AD but not in patients with normal cognition [40]. Frontal WMH is known to play a predominant role in motor dysfunctions in AD/aMCI patients [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with type 1 diabetes mellitus tend to develop WMH along with cognitive decline at a younger age than non-diabetic controls 27 . Ogama et al 28 found that postprandial hyperglycemia is related to WMH in diabetic patients with Alzheimer's disease while diabetic patients without dementia appeared to be less susceptible to the effects of hyperglycemia. Lacunar infarcts have been seen in patients with prediabetes and at an even higher number in patients with type 2 diabetes mellitus 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Retinal and brain neurodegenerative diseases although affecting different parts of the CNS, appear to involve similar pathogenic mechanisms like oxidative stress, low-grade chronic neuroinflammation, disruption of blood-brain or blood-retinal barrier, and vascular abnormalities (London et al, 2013; Colligris et al, 2018). Increasing clinical and preclinical evidence points to associations between metabolic dysregulation and neurodegenerative brain disease (Weinstein et al, 2015; Arnold et al, 2018; Ogama et al, 2018).…”
Section: Discussionmentioning
confidence: 99%